Transcatheter Aortic Valve Replacement of a Bicuspid Aortic Valve in a Heart Transplant Recipient - Beale, Robert (JACC Case Rep, 2020)
Patients with heart transplants who present with severe aortic stenosis may be deemed high-risk surgical candidates due to immunosuppression and multiple comorbid conditions. Appropriately selected patients may be successfully treated with transcatheter aortic valve replacement. (Level of Difficulty: Advanced.)